Plant diversity changes during the postglacial in East Asia: insights from Forest Refugia on Halla Volcano, Jeju Island - Dolezal, Jiri; Altman, Jan; Kopecky, Martin; Cerny, Tomas; Janecek, Stepan; Bartos, Michael; Petrik, Petr; Srutek, Miroslav; Leps, Jan; Song, Jong-Suk (PloS one, 2012)
Understanding how past climate changes affected biodiversity is a key issue in contemporary ecology and conservation biology. These diversity changes are, however, difficult to reconstruct from paleoecological sources alone, because macrofossil and pollen records do not provide complete information about species assemblages. Ecologists therefore use information from modern analogues of past communities in order to get a better understanding of past diversity changes. Here we compare plant diversity, species traits and environment between late-glacial Abies, early-Holocene Quercus, and mid-Holocene warm-temperate Carpinus forest refugia on Jeju Island, Korea in order to provide insights into postglacial changes associated with their replacement. Based on detailed study of relict communities, we propose that the late-glacial open-canopy conifer forests in southern part of Korean Peninsula were rich in vascular plants, in particular of heliophilous herbs, whose dramatic decline was caused by the early Holocene invasion of dwarf bamboo into the understory of Quercus forests, followed by mid-Holocene expansion of strongly shading trees such as maple and hornbeam. This diversity loss was partly compensated in the Carpinus forests by an increase in shade-tolerant evergreen trees, shrubs and lianas. However, the pool of these species is much smaller than that of light-demanding herbs, and hence the total species richness is lower, both locally and in the whole area of the Carpinus and Quercus forests. The strongly shading tree species dominating in the hornbeam forests have higher leaf tissue N and P concentrations and smaller leaf dry matter content, which enhances litter decomposition and nutrient cycling and in turn favored the selection of highly competitive species in the shrub layer. This further reduced available light and caused almost complete disappearance of understory herbs, including dwarf bamboo.
Keywords: klimatické změny; Trees; ledový příkrov; biodiverzita; Ice Cover; Republic of Korea; Volcanic Eruptions; Korejská republika; Ecosystem; stromy; sopečné erupce; ekosystém; Biodiversity; Climate Change